Risk of Depression and Post-Traumatic Stress Disorder among Adult Filipino Patients with Respiratory Allergies from an Allergy Unit in a Tertiary Hospital during the COVID-19 Pandemic: A Cross-sectional Study - Alip-Tambal, Pamela Noreen; Kwong-Buizon, Shirley (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Objectives: This study aimed to determine the risk of depression and post-traumatic stress disorder among Filipino adults with respiratory allergies in an allergy unit during the COVID-19 pandemic. Also, we sought to identify if certain demographic variables are associated with these mental health conditions. Methodology: Respondents from an allergy unit completed the online survey from January to May 2022. Data obtained included sociodemographic factors and the presence of respiratory allergies. Patient Health Questionnaire - 9 (PHQ-9) and Impact of Event Scale-Revised (IES-R) ratings were used to measure depression and risk of post-traumatic stress disorder (PTSD), respectively. The relative risk or risk ratio (RR) of depression and post-traumatic stress disorder (PTSD) among subjects and the influence of demographic characteristics, type, and severity on the risk of depression and post-traumatic stress disorder (PTSD) among the subjects were estimated using log-binomial regression. Results: A total of 173 respondents were included in the study: 92 with respiratory allergies and 80 without respiratory allergies. Compared to those without allergies, those with allergies had a much higher proportion of post-graduate degree and higher monthly income. Of the individuals, 40.12% suffered from allergic rhinitis, 3.49% from asthma, and 9.88% from both allergies. The mean PHQ-9 score for all respondents was 7.80 (SD = 6.23), with a mean score of 7.89 (SD = 6.34) and 7.72 (SD = 6.29) for those without and with respiratory allergies, respectively. Among those without respiratory allergies, 41.25% had mild depression, 12.50% had moderate depression, 11.25% had moderately severe depression, and 6.25% had severe depression. Among those with allergies, 33.70% had mild depression, and 19.57% had moderate depression. The mean score for the intrusion, avoidance, and hyperarousal subscales of the IES-R were 10.32 (SD = 6.34), 11.17 (SD = 7.21), and 6.99 (SD = 5.38), respectively, and the overall mean IES-R score for the respondents was 10.32 (SD = 7.34). Among those without respiratory allergies, 31.50% had high scores for PTSD, 2.50% had probable PTSD, 20% had PTSD as a clinical concern, and 46.25% did not have PTSD. For those with allergic rhinitis, the prevalence of high scores for PTSD was 40.58%, while it was 50.00% for those with asthma. Depression was highly correlated with age and marital status. For PTSD, those who were married (OR = 0.31, p = 0.012) were 3.23 times less likely to develop the condition than their single counterparts. The type of respiratory allergies, the severity of allergic rhinitis, and the level of asthma control were not significantly associated with the severity of depression and PTSD of any degree. Conclusion: Patients with respiratory allergies did not have an increased risk of depression and post-traumatic stress disorder in this particular population. The PHQ-9 AND IES-R scores among those with respiratory allergies and those without were shown to have no significant difference. Demographic factors found to be associated with depression were age and marital status, while for PTSD, it was only marital status. The type of respiratory allergy, control, and severity were not associated with depression and PTSD of any degree.